Implementation Of Modular Testing In Bios Development And Debug - Teh , Hong Hor (2014)
This project presents a modular approach in BIOS development in purpose to tackle the problem of long development time with the existing methodologies which are hardware platform approach and virtual platform approach. The proposed approach consists of previous generation platform, a FPGA card and UEFI drivers. The FPGA is loaded with the RTL of one Intellectual Property (IP) from the current company project. The chosen IP is Low Power Subsystem (LPSS). The card is then plugged into the PCI slot of the platform. Besides, UEFI Configuration Driver and UEFI Reset Driver are built to configure and reset the LPSS registers respectively. Both of them are stored into a thumb drive and plugged into USB port of the platform. They are executed in the UEFI Shell environment. In this project, the development time of LPSS needed by the three methodologies which are hardware platform approach, virtual platform approach and modular approach are compared. The results indicate that modular approach is capable to save up to 90% of the development time in comparison with the other two approaches. At the same time, both of the UEFI drivers are functioning correctly. The processing time of both of the UEFI Configuration Driver and UEFI Reset Driver are about 1 to 2 seconds only. In conclusion, the novelty of the modular approach is that the BIOS can be developed in modular basis, without having to develop the BIOS as a whole. Therefore, it is able to cut down the BIOS development time efficiently